Pengaruh Inovasi Produk Dan Lokasi Terhadap Keputusan Penelitian Konsumen Pada Roemah Bata Café & Resto Medan - Supri Mahendra; Muslim Wijaya; Syahriandy Syahriandy (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This study aims to determine "the influence of product and location innovation on consumer purchasing decisions at Roemah Bata Café Resto Medan". This type of research is an associative study, which is a study that asks about the relationship between two variables. The population in this study were 100 consumers who made transactions at Roemah Bata Café Resto Medan using the Slovin formula so as to obtain a sample of 80 consumers. Based on the results of the research, partially, the product innovation variable, the tcount value was 3,468, where the t-table value at α 5% was 1,664 and the p-value in the sig column was 0.001 0.005, which means that the product innovation variable had a positive and significant effect on consumer purchasing decision variables. Based on the results of the research, partially the location variable, the tcount value was 5.285 where the ttable value at α 5% was 1.664 and the p-value in the sig column 0.000 0.005 means that the location variable has a positive and significant influence on consumer purchasing decision variables. Based on the results of the study, simultaneously the value of fcount ftable is 39.228 3.12 and the p-value is obtained in the sig column 0.000 0.05, which means that the product innovation and location variables have a positive and significant influence on consumer purchasing decisions.